Development of Flipchart Media as a Classical Service Media to Improve Students' Understanding of Self Control - Rijaluddin Robbani; Nanang Erma Gunawan (Lembaran Ilmu Kependidikan, 2026)
This study developed the flipchart media as a media to assist classical services to improve students' understanding of self-control. The background of this research is the absence of a specially designed flipchart for classroom guidance, despite the fact that low self-control often leads to negative behaviors such as being easily provoked and having difficulty managing emotions. The research employed the R&D method with the ADDIE model, involving 48 eleventh-grade MAN students, two media experts, one subject matter expert, and trials in both experimental and control classes. Data were collected through questionnaires and analyzed using t-tests, N-gain, and homogeneity tests. The results indicated that the flipchart was rated “highly feasible,” had a practicality score of 92.46% (very practical), and demonstrated significant effectiveness (p = 0.000) with an N-gain of 1.07 (high category). The flipchart was declared effective and suitable for enhancing students’ self-control understanding.